Deep Venous Thrombosis and Lupus Anticoagulant - Simioni, Paolo; Prandoni, Paolo; Zanon, Ezio; Saracino, Maria A; Scudeller, Alberta; Villalta, Sabina; Scarano, Luigi; Girolami, Bruno; Benedetti, Lino; Girolami, Antonio (Thrombosis and Haemostasis, 1996)
Background. A definite evidence in favour of an association of deep-vein thrombosis (DVT) with lupus anticoagulant (LA) in patients free from systemic lupus erythematosus is still lacking.Methods. In a case-control study, LA was determined in 176 consecutive outpatients who underwent phlebography because of the first episode of clinically suspected DVT of lower limbs. The association between DVT and LA was described using odds ratios (OR).Results. Contrast venography confirmed the clinical suspicion in 59 patients (33.5%). LA was detected in 5 of the 59 patients with DVT (8.5%), and in none of the 117 subjects with normal venogram (P = 0.007). The OR for having an acute DVT in patients with LA was 10.7 (95% CI: 1.2-94.2).Conclusions. LA is significantly associated with DVT in symptomatic patients. Further studies are needed to establish the clinical implications of this association.